Coarse grained simulations of local anesthetics encapsulated into a liposome - Pickholz, Mónica Andrea (2010)
We investigated the encapsulation of prilocaine (PLC), an aminoamide local anesthetic widely used in dentistry, into a small unilamellar liposome. We extended a recently developed coarse grained model to access the problem relevant time and length scales. Molecular dynamics (MD) simulations for different protonation states of the PLC captured important features of the PLC−vesicle interactions. We found that all neutral PLC molecules (nPLC) rapidly diffuse into the hydrophobic region of the vesicle adopting an asymmetric bimodal density distribution, with nPLC molecules jumping between the internal and external vesicle monolayers. Protonated PLC molecules (pPLC) initially placed in water were instead only found on the external monolayer, with a high rate of exchange with the water phase and no access to the inner part of the liposome. Although electrostatic interaction between pPLC tails and oppositely charged lipid head groups is shown to be structured, hydrophobicity is the driving force of PLC drug absorption within the liposome. Our simulations also show that a major percentage of pPLC remains trapped within the interior water phase of the liposome when starting from a configuration with pPLC distributed within the lipid membrane. This suggests that at low pH liposome−PLC complexes and therefore drug efficacy can strongly depend on the preparation procedure.